UV LASER ABLATION AND IRM-GCMS MICROANALYSIS OF 18O/16O AND 17O/16O WITH APPLICATION TO A CALCIUM-ALUMINIUM-RICH INCLUSION FROM THE ALLENDE METEORITE - STRATEGIES FOR HIGH PRECISION AND ACCURACY WITH LASER HEATING - Young E.D.; Coutts D.W.; Kapitan D. (My University, 1998)
Analyses of 18O/16O and 17O/16O in silicate and oxide minerals by UV laser ablation of 100 x 80 x 50 μm sample pits combined with irm-GCMS yield precision and accuracy similar to that of conventional methods. This represents a 100-fold reduction in minimum size relative to other fluorination methods based on gas-source mass spectrometry and enables high-precision in-situ intracrystalline analysis of silicate minerals.Analyses of almandine, forsterite, and schorl of known isotopic compositions indicate an analytical precision of +/-0.3%% (1σ) in δ18O and +/-0.4 in δ17O with an accuracy of similar magnitude. Application to meteoritic samples is demonstrated by in-situ analysis of pyroxene and melilite from a type B CAI inclusion from the Allende meteorite. The CAI data adhere to the carbonaceous chondrite anhydrous mineral line defined by conventional macroscopic fluorination methods and demonstrate that non-mass dependent differences of 1%% amu-1 are discernible. The unique combination of analytical and spatial resolution afforded by the new UV laser microprobe will allow high-precision mapping of the distribution of anomalous oxygen in minerals from calcium-aluminum-rich inclusions on a previously unattainable scale.